Pengaruh Kualitas Produk, Kualitas Pelayanan dan Persepsi Harga terhadap Keputusan Pembelian di Kowok Coffee - Pioka Ardita; Salman Paludi (Indonesian Journal Publisher, 2025)
The purpose of this study was to determine how Kowok Coffee customers' perceptions of product quality, service quality, and price perception influence their purchasing decisions. With a total of 100 respondents, the population and sample in this study were all Kowok Coffee customers. The sampling method used was accidental sampling. Data collection was carried out accidentally using a questionnaire that had been tested for validity and reliability. Using SPSS software version 26, multiple linear regression analysis was used as a quantitative analysis tool. The results showed that product quality had a positive and significant effect on purchasing decisions, service quality had a positive and significant effect on purchasing decisions, and price perception had no significant effect on purchasing decisions. Simultaneously, product quality, service quality, and price perception had a positive and significant effect on purchasing decisions at Kowok Coffee. These results highlight the important role of product quality, service quality, and price perception in purchasing decisions. Therefore, it is important for management to maintain and improve these three aspects to maintain competitiveness and purchasing decisions. It is explained that management must consider aspects of product quality, service quality, and price perception because they can be an important part of purchasing decisions. This understanding is crucial for businesses in developing integrated and impactful marketing strategies to increase competitiveness in the market.